Comparação da razão carga-deflexão do fio flexy-multi® com fios de aço, beta-titânio e níquel-titânio de diversas marcas comerciais - Póvoa, Vinícius Marcelo Aires (2011)
Flexy-Multi™, a newly introduced finishing wire with the outermost portion of its crosssection composed by nickel-titanium and its core by beta-titanium, was evaluated according to its flexural behavior in bending tests. The aim of this study was to compare the loaddeflection rate of Flexy-Multi™ to stainless-steel, beta titanium and nickel-titanium archwires in three-point bending test. The samples examined included 0.017”x 0.025”-inch stainlesssteel, beta-titanium, nickel-titanium and Flexy-Multi™ wires. Each combination, alloy and manufacturer, was tested 6 times and an average was obtained for comparison. All specimens were tested in a universal testing machine (EMIC DL10.000/700) in a 3-point bending test at a speed of 1mm per minute and deflected for 1.5 mm. Loading and unloading forces were recorded at each 0.5mm of deflection and load-deflection curves were determined. Three self-ligating brackets of lower incisors (In-Ovation – GAC Orthodontics, Roth prescription, slot .022”x.028”) were used as supports to the wires. On loading, there was no difference between Flexy-Multi™ and all nickel-titanium wires tested. On the other hand, Flexy-Multi™ showed lower load-deflection rates than all stainless-steel and betatitanium wires both on loading and unloading (p>0.05). On unloading, Flexy-Multi™ showed lower load-deflection rate than all nickel-titanium wires just to 0.5mm of deflection (p<0.05). Flexy-multi™ presented a lower load-deflection rate than all wires tested, except when compared to nickel-titanium where this difference came up just at the level of 0.5mm of unloading, since this wire lost force by the end of the test.